Comparison of different subanaesthetic ketamine doses on perioperative opioid consumption in major gynaecological surgery - Kamaruzaman, Puteri Nadia (2020)
Background: Ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, at a subanaesthetic dose (lower dose), has been used preemptively as an adjuvant to analgesic treatment. In majority of studies, the effective intraoperative bolus doses used are from 0.15 mg/kg to 0.5 mg/kg and infusions in the range of 0.12-0.2 mg/kg/h. CNS manifestation incidence is higher at doses above 0.3 mg/kg, thus this is considered as the upper limit for bolus doses, but the lower limit has not been studied. The aim of this study is to evaluate whether a lower dose of ketamine 0.075mg/kg bolus with infusion of 0.06mg/kg/h (1mcg/kg/min) will offer the same reduction in perioperative opioid consumption as compared to the current lower limit of 0.15mg/kg bolus with infusion of 0.12mg/kg/h (2mcg/kg/min). Methods: 80 adult female patients who underwent elective major gynaecology surgery in Hospital Universiti Sains Malaysia and Hospital Sultanah Bahiyah, Alor Setar, Kedah were randomly assigned to receive either Group A: (ketamine 0.15mg/kg IV bolus + 0.12mg/kg /h infusion (2mcg/kg/min)) or Group B: (ketamine 0.075mg/kg IV bolus + 0.06mg/kg /h infusion (1mcg/kg/min)). The measured outcomes were: 1. The mean total opioid consumption during the intraoperative period, 2. The mean total opioid consumption within 24 hours after surgery, 3. The mean time for first patient-controlled analgesia (PCA) demand between the two groups and 4. The mean numerical rating scale (NRS) of pain score at 2 hours, 6 hours, 12 hours and 24 hours post-surgery. Other outcomes monitored include the intraoperative hemodynamic status and presences of CNS manifestation (vivid dreams, hallucinations, confusion and irrational behaviour). Results: There were no significant statistical difference between group A and B in terms of total opioid consumption (morphine) 24 hours postoperatively (p= 0.477), meantime for first patient-controlled analgesia (PCA) demand (p=0.22) and mean numerical rating scale (NRS) at 2 hour (p=0.182), 6 hour (p=0.58), 12 hour (0.149) and 24 hour (p=0.521). However, there was a significant statistical difference in the mean intraoperative fentanyl consumption, where group A had lower mean fentanyl consumption of 26.25 ug ± 49.3 compared to group B of 50ug ± 55.7 with a p-value 0.047. With prolong ketamine infusion at 2 hours, there was a lower mean MAP in ketamine Group A (mean=89.52mmHg, SD=11.03) compared to Group B (mean=97.07mmHg, SD=5.19) and a p=0.008. However, there was no significant statistical difference in the mean MAP at baseline, 10 min and 1 hour. Both groups had no reported CNS manifestation. Conclusion: We recommend to adhere to the current dose of IV ketamine bolus of 0.15mg/kg and infusion of 0.12mg/kg/h (2mcg/kg/min) as at this dose, intraoperative opioid consumption is lower. Nevertheless, a bolus of 0.075mg/kg and infusion of 0.06mg/kg/h (1mcg/kg/min) may hold promise as even at this very low dose, this regime showed similar results to standard dose in terms of postoperative opioid requirement, first analgesic request and pain score. However, further research is needed to confirm the current findings.